2018
DOI: 10.1097/gco.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

The use of technology in the sexual health education especially among minority adolescent girls in the United States

Abstract: Ultimately, more research needs to be conducted to determine the most effective content for these sexual health apps. Additionally, more research should be conducted on effective sexual health apps for marginalized populations to determine whether technology is a viable solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 18 publications
(12 reference statements)
0
18
0
5
Order By: Relevance
“…Some previous research has found that technology-based programming is relevant for Black and Latinx teens [ 16 , 17 , 18 ]. For example, a previous evaluation of Pulse, an app-based sexual and reproductive health intervention implemented with women aged 18–20 who were recruited online, found several promising preliminary impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous research has found that technology-based programming is relevant for Black and Latinx teens [ 16 , 17 , 18 ]. For example, a previous evaluation of Pulse, an app-based sexual and reproductive health intervention implemented with women aged 18–20 who were recruited online, found several promising preliminary impacts.…”
Section: Introductionmentioning
confidence: 99%
“…The desire to conceal their identity may be of particular importance to adolescents who may not want their parents or friends to know that they are engaged in a sexual health education program. Anonymity has been found to increase participation in new media sexual health interventions among other at-risk groups, including adolescents and emerging adults [ 42 ] and adolescent women of color [ 43 ]. The decreased chances of undesired participant identification, in addition to convenience (ie, no travel requirements or synchronous login requirements) may make new media a better delivery mechanism for sexual health interventions than traditional face-to-face intervention delivery methods for some at-risk adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…They could also provide resources (e.g., educative websites, clinics, feminist sex shops) or help create platforms for people to meet, build communities, discuss sexuality, and feel validated. Sex education is unevenly distributed in the world, but if we favor inclusivity and accessibility [ 164 ], technology can once again democratize this important service [ 40 , 100 , 289 ].…”
Section: Beneficial Erotic Machinesmentioning
confidence: 99%